2001
DOI: 10.1111/j.1346-8138.2001.tb00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin Metastasis of Neuroendocrine Carcinoma Derived from the Mediastinum

Abstract: We report a 46-year-old Japanese man with a metastatic skin tumor on his left palmar region. He underwent resection for a mediastinal neuroendocrine carcinoma in February of 1998. After the operation, he immediately noticed an elevated tumor on his left palm. In September 1999, a brain tumor was discovered. The skin and brain tumors were subsequently removed surgically. Neuron specific enolase (NSE) in the serum was elevated to 25 ng/ml. A skin biopsy specimen from the left palmar site revealed multiple tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Chan et al 6 reported that cytokeratin 20 was a useful marker to distinguish these conditions. Most metastatic NECs do not express cytokeratin 20, with the exception of cutaneous NEC derived from the mediastinum 4 and salivary gland 6 . Immunostaining tests performed on cells of our patient were compatible with diagnosis of metastatic NEC.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Chan et al 6 reported that cytokeratin 20 was a useful marker to distinguish these conditions. Most metastatic NECs do not express cytokeratin 20, with the exception of cutaneous NEC derived from the mediastinum 4 and salivary gland 6 . Immunostaining tests performed on cells of our patient were compatible with diagnosis of metastatic NEC.…”
supporting
confidence: 57%
“…Cutaneous histological findings of undifferentiated small‐cell carcinoma with neuroendocrine features can be seen in Merkel cell carcinoma or in secondary metastasis from some visceral origin. The primary sites of origin include the lung, 2 larynx, 3 mediastinum, 4 uterus, 1 and thymus 5 . Microscopically, organoid clusters, trabeculae, and sheets of small hyperchromatic cells with scant cytoplasm, and round‐to‐angulated nuclei, characterize the architectural patterns of growth 5 .…”
mentioning
confidence: 99%
“…Reports of widespread multiple cutaneous metastases of primary neuroendocrine carcinomas, including respiratory and genitourinary, are very rare in the human literature. In people, the identified sites of the primary tumors are the larynx, lung, 2,3 mediastinum, urinary bladder, 26 uterus, or uterine cervix. 6,8,9 Although a major limitation in the present case is the absence of a full necropsy evaluation, the presence of a single large tumor in the nose and multiple smaller, uniformly sized tumors in the dermis is highly suggestive of a primary nasal tumor with cutaneous metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible primary sites of neuroendocrine carcinomas that may develop metastasis to the skin, described in indexed literature are lung, 1 mediastinum, 5 uterus, 6 and thymus 1…”
Section: Discussionmentioning
confidence: 99%